Updated checklist of bony fishes along the Libyan coasts (Southern Mediterranean Sea) - ELBARAASI, HOUSSEIN; ELABAR, BAHRIA; ELAABIDI, SALAMA; BASHIR, ASMA; ELSILINI, OSAMA; SHAKMAN, ESMAIL; AZZURRO, ERNESTO (Mediterranean Marine Science, 2019)
Here we provide an updated review of both native and non-indigenous ichthyofauna occurring in the waters of Libya, one of the largest and less studied marine areas of the Mediterranean basin. With respect to the most recent information, the list of Libyan bony fishes was updated with 104 species for a total of 304 listed taxa. Out of these species, 271 are native, 6 endemic to the Mediterranean, 22 non indigenous of Lessepsian origin and 5 range expanding taxa from Gibraltar. Information on the distribution and abundance of Lessepsian fishes along the Libyan coasts was gained through both field surveys and interviews with local small-scale fishermen, which contributed in filling large information gaps in the area. This combined approach allowed to gather a more complete representation of non indigenous species along the Libyan coasts and indicated three assessment areas, corresponding to the eastern, central and western sectors of the country, which should be considered in future monitoring programs.